Premature ejaculation and stress - Fiala, Ludek; Lenz, Jiri; Konecna, Petra; Zajícová, Markéta; Cerna, Jana; Sajdlová, Rachel (Andrologia, 2021)
Recent findings indicate that men with premature ejaculation report more frequent sexual problems associated with increased anxiety and interpersonal difficulties. Bearing this in mind, the neuroendocrine changes were examined in men with premature ejaculation and compared to other indicators of stressful experiences to see whether there can be any correlation which could indicate how these factors may contribute to the aetiology of premature ejaculation. Our study comprised 60 male outpatients diagnosed as having secondary premature ejaculation. Clinical examinations were focused on biochemical analysis of cortisol and psychometric scoring using a diagnostic tool for premature ejaculation, traumatic stress and somatoform dissociation. The control group consisted of a 60 healthy men. The results showed significant Spearman correlations of the Premature Ejaculation Diagnostic Tool score with Trauma Symptom Checklist score (R = .86), cortisol level (R = .47) and Somatoform Dissociation Questionnaire score (R = .61). In the control group, the results did not reach statistical significance. Spearman correlations of the Premature Ejaculation Diagnostic Tool score with Trauma symptoms checklist score was (R = .21), cortisol (R = .27) and with Somatoform dissociation questionnaire score (R = .25). These results represent the first reported findings documenting the relationship of traumatic stress indicators with the experience of secondary premature ejaculation and cortisol levels.
Keywords: předčasná ejakulace; Premature Ejaculation; ejakulace; úzkost; mužské pohlaví; Ejaculation; průzkumy a dotazníky; Anxiety; Humans; lidé; Surveys and Questionnaires; Male